2010
DOI: 10.1521/aeap.2010.22.4.328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a U.S. Evidence-Based Parenting Intervention in Rural Western Kenya: From Parents Matter! to Families Matter!

Abstract: We evaluated Families Matter! Program (FMP), an intervention designed to improve parent-child communication about sexual risk reduction and parenting skills. Parents of 10- to 12-year-olds were recruited in western Kenya. We aimed to assess community acceptability and FMP's effect on parenting practices and effective parent-child communication. Data were collected from parents and their children at baseline and 1 year postintervention. The intervention's effect was measured on six parenting and parent-child co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 34 publications
2
59
1
Order By: Relevance
“…Recent quantitative studies in rural and urban Nigeria found that men were generally not involved in FP decision-making despite their partners' wishes (Ijadunola et al, 2011;Ogunjuyigbe, Ojofeitimi, & Liasu, 2009;Utoo, Mutihir, & Utoo, 2010). Other qualitative studies from rural Tanzania also demonstrate that although men dominate several aspects of social life, they do not participate in decision-making around childbearing (Keele, Forste, & Flake, 2005, Wight, Plummer, & Ross, 2012. Furthermore, qualitative studies conducted among rural sub-Saharan African men revealed that men do not accept hormonal contraceptive use due to fear of side effects (Chipeta et al, 2011;Wambui, Ek, & Alehagen, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent quantitative studies in rural and urban Nigeria found that men were generally not involved in FP decision-making despite their partners' wishes (Ijadunola et al, 2011;Ogunjuyigbe, Ojofeitimi, & Liasu, 2009;Utoo, Mutihir, & Utoo, 2010). Other qualitative studies from rural Tanzania also demonstrate that although men dominate several aspects of social life, they do not participate in decision-making around childbearing (Keele, Forste, & Flake, 2005, Wight, Plummer, & Ross, 2012. Furthermore, qualitative studies conducted among rural sub-Saharan African men revealed that men do not accept hormonal contraceptive use due to fear of side effects (Chipeta et al, 2011;Wambui, Ek, & Alehagen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Most Tanzanian studies focus on young women, and those that include young men generally take place in rural settings (Larsen & Hollos, 2003;Marchant et al, 2004;Wight et al, 2006Wight et al, , 2012. Thus, urban studies are needed that include the perspective of both young adult men and women on contraceptive use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is relatively little information in the literature to guide the process by which such adaptations can be accomplished (Chu, Huynh, & Arean, 2012), and most of the available articles describe adaptation across different subpopulations within the U.S. (Cardona et al, 2012;Goodkind, Lanoue, & Milford, 2010;Hitt et al, 2006;Hurd, Valerio, Garcia, & Scott, 2010;Kim & McKay-Semmler, 2013). Almost no articles in the literature address international adaptations of HIV/AIDS prevention programs (Poulsen et al, 2010;Vandenhoudt et al, 2010).…”
mentioning
confidence: 99%